2017
DOI: 10.1515/acph-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release biodegradable solid lipid microparticles: Formulation, evaluation and statistical optimization by response surface methodology

Abstract: Sustained release biodegradable solid lipid microparticles: Formulation, evaluation and statistical optimization by response surface methodologyFor preparing nebivolol loaded solid lipid microparticles (SLMs) by the solvent evaporation microencapsulation process from carnauba wax and glyceryl monostearate, central composite design was used to study the impact of independent variables on yield (Y 1 ), entrapment efficiency (Y 2 ) and drug release (Y 3 ). SLMs having a 10-40 µm size range, with good rheological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The XRD study was done to evaluate the physical nature of the drug and the effect of the method of preparation and excipients [ 95 , 96 ]. Figure 5 presents the XRD of NVH, CSL, NVH:CSL physical mixture (2:5) and the lyophilized best-achieved formulation F6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD study was done to evaluate the physical nature of the drug and the effect of the method of preparation and excipients [ 95 , 96 ]. Figure 5 presents the XRD of NVH, CSL, NVH:CSL physical mixture (2:5) and the lyophilized best-achieved formulation F6.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 presents the XRD of NVH, CSL, NVH:CSL physical mixture (2:5) and the lyophilized best-achieved formulation F6. NVH had sharp intense peaks at 5.9°, 11.9°, 12.2°, 16.3°, 18.4°, 21.4°, 22.4°, and 25.67°, confirming its crystalline form [ 95 , 96 , 97 ]. The X-ray spectra of the physical mixture showed that the NVH peaks intensity decreased, possibly due to the dilution effect, without a qualitative disparity of its diffractogram.…”
Section: Resultsmentioning
confidence: 99%